2008
DOI: 10.1152/ajpheart.00790.2008
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial ischemia-mediated excitatory reflexes: a new function for thromboxane A2?

Abstract: Fu LW, Phan A, Longhurst JC. Myocardial ischemia-mediated excitatory reflexes: a new function for thromboxane A 2? Am J Physiol Heart Circ Physiol 295: H2530 -H2540, 2008. First published October 24, 2008 doi:10.1152/ajpheart.00790.2008.-Clinical and experimental evidence has shown that myocardial ischemia activates cardiac spinal afferents that mediate sympathoexcitatory reflex responses. During myocardial ischemia, thromboxane A 2 (TxA2) is released in large quantities by activated platelets in the coronary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 52 publications
0
26
0
Order By: Relevance
“…The exercise pressor reflex was evoked by electrical stimulation of the cut peripheral ends of the left L 4 and L5 ventral roots (1-3 times motor threshold, 0.1-ms pulse duration, 40 Hz) for 30 s. TP receptors in the left hindlimb were blocked by injecting daltroban (80 g), a TP receptor antagonist, into the arterial supply of the left hindlimb (8,47). Before injection, the balloon occluder on the abdominal aorta and inferior vena cava was inflated to trap the injectate within the circulation of the left hindlimb.…”
Section: Experimental Protocolsmentioning
confidence: 99%
“…The exercise pressor reflex was evoked by electrical stimulation of the cut peripheral ends of the left L 4 and L5 ventral roots (1-3 times motor threshold, 0.1-ms pulse duration, 40 Hz) for 30 s. TP receptors in the left hindlimb were blocked by injecting daltroban (80 g), a TP receptor antagonist, into the arterial supply of the left hindlimb (8,47). Before injection, the balloon occluder on the abdominal aorta and inferior vena cava was inflated to trap the injectate within the circulation of the left hindlimb.…”
Section: Experimental Protocolsmentioning
confidence: 99%
“…10) causes arrhythmia (Wacker et al, 2009). TP receptors are also located on afferent sympathetic nerve endings in the heart and may participate in the sympathoexcitatory reflex that occurs during myocardial ischemia (Fu et al, 2008).…”
mentioning
confidence: 99%
“…Microinjection of Kyn into the elPBN reversibly attenuated BK-induced reflex responses in four vagus intact animals. These data are the first to show that NMDA and AMPA ionotropic glutamate receptors in the elPBN play an important role in processing cardiac excitatory reflex responses.2-amino-5-phosphonopentanoic acid; 2,3-dihydroxy-6-nitro-7-sulfamoyl-benzol(F)quinoxaline; bradykinin; renal sympathetic nerve activity ACTIVATION OF CARDIAC SPINAL (sympathetic) sensory nerve endings during myocardial ischemia by ischemic metabolites, such as thromboxane A 2 and bradykinin (BK), evokes sympathoexcitatory reflex responses, including hypertension and tachyarrhythmias as well as increases in sympathetic outflow (11,12,14,21,53). Clinical and experimental studies (13,35,52,60) have demonstrated that these reflexes significantly contribute to the development of lethal ventricular arrhythmias and heart failure, ultimately increasing morbidity and mortality of patients.…”
mentioning
confidence: 99%